A single UDP-galactofuranose transporter is required for galactofuranosylation in Aspergillus fumigatus - Engel, Jakob; Schmalhorst, Philipp Sebastian; Dörk-Bousset, Thilo (The journal of biological chemistry, 2009)
Galactofuranose (Galf) containing molecules have been described at the cell surface of several eukaryotes and shown to contribute to the virulence of the parasite Leishmania major and the fungus Aspergillus fumigatus. It is anticipated that a number of the surface glycoconjugates such as N-glycans or glycolipids are galactofuranosylated in the Golgi apparatus. This raises the question of how the substrate for galactofuranosylation reactions, UDP-Galf, which is synthesized in the cytosol, translocates into the organelles of the secretory pathway. Here we report the first identification of a Golgi-localized nucleotide sugar transporter, named GlfB, with specificity for a UDP-Galf. In vitro transport assays established binding of UDP-Galf to GlfB and excluded transport of several other nucleotide sugars. Furthermore, the implication of glfB in the galactofuranosylation of A. fumigatus glycoconjugates and galactomannan was demonstrated by a targeted gene deletion approach. Our data reveal a direct connection between galactomannan and the organelles of the secretory pathway that strongly suggests that the cell wall-bound polysaccharide originates from its glycosylphosphatidylinositol-anchored form.